Kesaksian Iman dalam Dialog Interreligius dan Teologi Interkultural: Witness Of Faith In Interreligious Dialogue And Intercultural Theology - Edy Syahputra Sihombing (Societas Dei: Jurnal Agama dan Masyarakat, 2020)
The witness of faith is an important element in interreligious dialogue to nourish the existence of theology in intercultural contexts. But dialogue tends to be understood as merely sharing truth information and doctrines in various religions. Such model dialogue is actually not relevant in religious plurality. On the other hand, there are challenges to creating dialogue, including: arrogance, closed attitudes, and claims of truth absolutism. Such a situation does not foster theology in an intercultural context. Humility is the key to dialogue, and the witness of faith plays an important role in nourishing theology in intercultural contexts. In interreligious dialogue, the important witness of faith today is living and practicing the authentic teachings of every religion, such as living in peace, harmony of fraternity, building wisdom of love, and creating justice. This paper will explore the significance of faith witness-ing in interreligious dialogue and intercultural theology with literature research methods to offer implementative recommendations. Keywords: faith witness; dialogue; interreligious; intercultural; theology